Efektifitas Kelompok Pengolah Hasil Perikanan Pasca Program CCDP - IFAD Di Kota Parepare - Farid Mahzar; Abdul Azis Ambar; Abdullah B (Jurnal Perikanan dan Kelautan, 2022)
Community empowerment through the CCDP - IFAD program is considered to be at least helpful in the efforts of the Regional Government to improve the standard of living of coastal communities, including those who still experience difficulties in gaining access to capital in the development of their productive economic activities. The purpose of the study was to analyze the effectiveness of fishery product processing groups after the CCDP-IFAD program ended in Parepare City. In assessing the effectiveness of the program, the study refers to the Decree of the Minister of Home Affairs No.690.900.327 of 1996. The results of the research group processing fishery products after the CCDP-IFAD program ended fairly effectively interms of availability of raw materials (83.52), production (84.21), and frequency of activities (83.90). Just a few groups of fishery products processors experienced increased productivity after the CCDP-IFAD programended.